THE INFLUENCE OF SERVICE TO CUSTOMER SATISFACTION IN DIRAJA HOTEL - Wasilatun Nikmah; Isyana Emita; Asadul Usud Boyratan (Kusuma Negara Business School, 2019)
Service has a very important role in the industry that is engaged in services, including hotel lodging services. Attention to the interests of customers by looking at the needs and satisfaction of service is a major factor in business success amid increasingly fierce competition. Therefore, realizing the importance of the value of service quality in order to increase customer satisfaction makes the company have to develop good business and customer relationships. The study uses quantitative descriptive analysis, with observational methods, questionnaires and documentation to 100 respondents and the sampling technique uses incidental sampling, which is a sampling technique based on chance. Data processing using SPSS version 23.0. Based on the analysis and processing of data according to the calculation of the correlation coefficient, it is known that Service to Customer Satisfaction has a strong relationship that is 0.786 and according to the calculation formula the coefficient of determination can be seen that by 59.4% and the remaining 40.6% is influenced by other factors, then the regression effect namely Y = 23,438 + 0.462 X. This equation shows that the service is constant or 0, then Y (Customer Satisfaction) is 23,438. The regression coefficient of 0.462 states that each addition of 1 to service will increase customer satisfaction by 0.462. Where Y = Customer Satisfaction and X = Service.